Burn-out et travail social : Du changement aux résistances à l'épreuve - Ben Mrad, Fatih (L'Harmattan, 2017)
Le burn-out est devenu un sujet rebattu. Le sous-titre de ce livre traduit la volonté de l'auteur de s'intéresser à la manière dont certains professionnels sont affectés par leur situation, des points de vue physique, psychologique et social. Quels sont les changements personnels que les individus connaissent lorsqu'ils sont confrontés à l'expérience d'un burn-out et lorsqu'ils doivent déployer certaines de leurs ressources pour résister et faire face à leur situation ? A partir de ses observations, l'auteur propose de mieux considérer certains éléments minorés dans les travaux internationaux sur le sujet.
Keywords: 2000 à aujourd'hui; 2010-2019; cours; cycles supérieurs; discipline; europe; fem7000; périodes historiques; régions géographiques; santé; santé mentale; sciences humaines; sofia; thématiques; travail; travail social

Epistemic Injustice and Illness - Kidd, Ian James; Carel, Havi (Journal of Applied Philosophy, 2017)
This article analyses the phenomenon of epistemic injustice within contemporary healthcare. We begin by detailing the persistent complaints patients make about their testimonial frustration and hermeneutical marginalization, and the negative impact this has on their care. We offer an epistemic analysis of this problem using Miranda Fricker’s account of epistemic injustice. We detail two types of epistemic injustice, testimonial and hermeneutical, and identify the negative stereotypes and structural features of modern healthcare practices that generate them. We claim that these stereotypes and structural features render ill persons especially vulnerable to these two types of epistemic injustice. We end by proposing five avenues for further work on epistemic injustice in healthcare.
Keywords: amériques; approches et analyses; capacitisme; capitalisme; care; corps; cours; cycles supérieurs; discipline; europe; fem9000; injustices herméneutiques; injustices testimoniales; injustices épistémiques; philosophie; racisme; royaume-uni; régions géographiques; santé; sciences humaines; sexisme; systèmes d'oppressions; thématiques; violences; états-unis

The Routledge handbook of epistemic injustice - Kidd, Ian James; Medina, José; Pohlhaus, Gaile M. (Routledge, 2017)
In the era of information and communication, issues of misinformation and miscommunication are more pressing than ever. Epistemic injustice–one of the most important and ground-breaking subjects to have emerged in philosophy in recent years–refers to those forms of unfair treatment that relate to issues of knowledge, understanding, and participation in communicative practices. The Routledge Handbook of Epistemic Injustice is an outstanding reference source to the key topics, problems, and debates in this exciting subject. The first collection of its kind, it comprises over thirty chapters by a team of international contributors, divided into five parts: Core Concepts; Liberatory Epistemologies and Axes of Oppression; Schools of Thought and Subfields within Epistemology; Socio-political, Ethical, and Psychological Dimensions of Knowing; Case Studies of Epistemic Injustice. As well as fundamental topics such as testimonial and hermeneutic injustice and epistemic trust the Handbook includes chapters on important issues such as social and virtue epistemology, objectivity and objectification, implicit bias, and gender and race. Also included are chapters on areas in applied ethics and philosophy, such as law, education, and healthcare. The Routledge Handbook of Epistemic Injustice is essential reading for students and researchers in ethics, epistemology, political philosophy, feminist theory, and philosophy of race. It will also be very useful for those in related fields, such as cultural studies, sociology, education, and law.
Le chap 10 de Patricia Hill Collins, “Intersectionality and Epistemic Injustice” a été donné en lcture au cours FEM9000. Le chap 14 de Kim Hall, “Queer Epistemology and Epistemic Injustice” a été donné en lecture au cours FEM9000. Le chap 15 de Rachel McKinnon, “Allies behaving badly: Gaslighting as epistemic injustice” a été donné en lecture au cours FEM9000. Le chap 16 de Shelley Tremain, “Knowing Disability Differently” a été donné au cours FEM9000. Le chap 33 de Anastasia Scrutton, “Epistemic Injustice and Mental Illness” a été donné en lecture au cours FEM9000. Le chap 34 de Rebecca Tsosie, “Indigenous peoples, anthropology, and the legacy of epistemic injustice” a été donné au cours FEM9000.
Keywords: approches et analyses; capacitisme; cours; cycles supérieurs; discipline; fem9000; hétérosexisme; injustices épistémiques; intersectionnalité; outils; ouvrages de références; philosophie; racisme; santé; sciences humaines; sexisme; systèmes d'oppressions; thématiques; violences; épistémologie; éthique; études critiques de la race; études critiques du handicap